2016
DOI: 10.1139/cgj-2015-0569
|View full text |Cite
|
Sign up to set email alerts
|

A strength criterion for frozen sodium sulfate saline soil

Abstract: Salt content has been proven to be an important influencing factor on the mechanical properties of frozen saline soils, whose strength criterion is different from that of unfrozen saline soils or frozen soils without salts. In this paper, a series of conventional triaxial tests are carried out for frozen saline soils with sodium sulfate at a temperature of -6°C. A strength criterion of the frozen saline soils, including the influence of salt content, is established by using the generalized nonlinear strength t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 35 publications
0
20
1
Order By: Relevance
“…With respect to frozen soils, the bonding e ect of ice crystals and soil particles possesses tensile strength, which will be weakened due to the pressure melting under relatively high con ning pressures, similar to the cohesive behaviors of cemented clay. In the previous study [13,14,17,18,37], it is indicated that the strength of frozen soils increases rst and then decreases with the increase of con ning pressures. e maximum value q max of the q-p curve corresponds to failure mean stress p cr .…”
Section: A New Strength Criterion For Frozen Sandy Soilmentioning
confidence: 96%
See 3 more Smart Citations
“…With respect to frozen soils, the bonding e ect of ice crystals and soil particles possesses tensile strength, which will be weakened due to the pressure melting under relatively high con ning pressures, similar to the cohesive behaviors of cemented clay. In the previous study [13,14,17,18,37], it is indicated that the strength of frozen soils increases rst and then decreases with the increase of con ning pressures. e maximum value q max of the q-p curve corresponds to failure mean stress p cr .…”
Section: A New Strength Criterion For Frozen Sandy Soilmentioning
confidence: 96%
“…Later, Nguyen et al [42] proposed that the CSL of the cemented clay eventually reduced to an asymptote coinciding with the CSL of natural clay. Lai et al [17] and Liao et al [18] employed a modi ed mean e ective stress expression to describe the strength criterion for frozen soils.…”
Section: A New Strength Criterion For Frozen Sandy Soilmentioning
confidence: 99%
See 2 more Smart Citations
“…Massive infrastructures have been designed and constructed in Northern China, such as the West-East electricity transmission project, and have to face the problematic soils, e.g., coarse-grained saline soils, especially those distributed in the Gobi Desert or the desert margin in inland areas [1,2]. e coarse-grained saline soils experienced cyclic salification and desalination due to complex processes that salt in soils periodically exists in crystalline or dissolved state, accompanied by a continuing migration and accumulation of dissolved salt, resulting in particular engineering properties [3,4].…”
Section: Introductionmentioning
confidence: 99%